Processing of Enriched Pear Slices with Blueberry Juice: Phenolics, Antioxidant, and Color Characteristics - Siluana Katia Tischer Seraglio; Belkis Sarahí Hernández-Velásquez; Moira Elizabeth Osses-Millar; Bárbara Yolanda Malverde-Muñoz; María Estuardo Guerra-Valle; Constanza Pavez-Guajardo; Jorge Moreno (MDPI AG, 2023)
This study evaluated the effectiveness of phenolic compound incorporation from blueberry juice into pear slices (PS) using a combination of ohmic heating (OH) and vacuum impregnation (VI), followed by air-drying (AD) or freeze-drying (FD). Our results showed that OH increased the content of bioactive compounds and antioxidant capacity of blueberry juice, with the optimal OH condition set at 50 °C for 20 min under an electric field of 13 V·cm−1. Furthermore, the combination of VI and OH was efficient in enriching PS with bioactive compounds from blueberry juice (such as cyanidin and epigallocatechin), with the optimal VI/OH condition set at 50 °C for 90 min under an electric field of 7.8 V·cm−1. Moreover, anthocyanin pigments from blueberry juice affected the color parameters of PS by increasing the a* parameter and decreasing the b* and L* parameters. However, both FD and AD (at 40, 50, and 60 °C) negatively affected (p ≤ 0.05) the phenolic content and antioxidant capacity. Notably, AD at 60 °C showed the highest levels of phenolic compounds and antioxidant potential for both impregnated and non-impregnated PS.